Gambaran Klinis dan Histopatologi Karsinoma Prostat di Salah Satu RS Swasta Jakarta Barat Tahun 2021-2023 - Firman Kevin Gratio Nainggolan; Christina, Shintia; Boedijono, Freciyana; Angeline, Reni (Jurnal MedScientiae, 2025)
Prostate carcinoma is a type of cancer that occurs in the prostate gland in men. Globally, in 2022, 14,2% of prostate cancer cases were recorded in the male population. In the Indonesian male population, there were 7,0% of prostate cancer cases. This study aims to determine the clinical and histopathological features of prostate carcinoma patients at one of Jakarta Barat private hospital in 2021–2023..This study is a descriptive study with a retrospective approach at one of private hospital in West Jakarta. Determination of sample size using consecutive sampling technique with a sample size of 79 samples. The most cases of carcinoma were recorded in 2021 with 35 samples (44,3%). In this study, there were 36 cases in the age range >70–80 years (45,6%). The most common clinical complaint was LUTS with 54 samples (68,4%). The most common sampling technique was TRUS-biopsy with 35 samples (44,3%). The results of histopathological examination were dominated by acinar adenocarcinoma with 72 samples (91,1%). A total of 27 samples were Gleason Class Group 5 (34,2%). The incidence of prostate carcinoma at one of Jakarta Barat private hospital in 2021-2023 was 79 samples with the most common complaint being LUTS. The most common incidents occurred in the age range of >70-80 years. The most frequently used method of sampling was TRUS-biopsy with acinar adenocarcinoma being the most common histopathological result found and Gleason Grade Group 5 dominating in this study.